Designing an Engineering Laboratory Course for Problem Based Learning - Gesualdo, Edson; Maximiliam, Luppe; Oliveira, Vilma A. (Journal of Engineering Education Transformations, 2025)
This work presents a proposal for implementing a problem-based learning (PBL) methodology by means of a new specific engineering course. Using interesting and practical projects, this specific course integrates engineering courses of different. However, each involved engineering course maintains its respective syllabus and the methodological freedom of the lecturers. The lecturers can further explore the subjects by introducing methodological innovation. The selected projects will highlight how the topics learned can be used to understand the problem being studied and to find the solution. The proposed course will bring together the participants in the form of seminars to analyze the problems and the solutions, checking their mistakes and the possibility of them being implemented. The study object is the competition vehicle SAE Mini Baja developed by EESC USP Baja SAE team, which will provide case studies associated with practical needs in a competitive environment.